ANALISIS SINYAL GEDUNG C FKIP UNTIRTA MENGGUNAKAN METODE PROTOKOL TCP DAN UDP - Avisa Marella; Didik Aribowo (Universitas Lampung, 2025)
In this study, both TCP and UDP protocols were used to analyze signal quality in Building C of FKIP UNTIRTA; TCP is known for maintaining data accuracy, while UDP offers higher transfer speeds but carries a greater risk of data loss. Measurements included signal strength, delay, jitter, and packet loss rate. The results showed that TCP is more stable but experiences greater delay, whereas UDP provides faster transmission. The choice of protocol should be adjusted based on application requirements. It is expected that this study will serve as a reference for optimizing the network in Building C of FKIP according to the needed service characteristics.